Solvent effect in 1H NMR spectra of 3'-hydroxy-4'-methoxy isoflavonoids from Astragalus membranaceus var. mongholicus - Du, Xingang (Magnetic resonance in chemistry : MRC, 2006)
Copyright (c) 2006 John Wiley & Sons, Ltd.